2014
DOI: 10.1186/2193-9020-3-18
|View full text |Cite
|
Sign up to set email alerts
|

Gender and ethnic inequalities in LAC countries

Abstract: This article examines the structure of gender and ethnic wage gaps and the distribution of both paid and unpaid work in LAC countries. Its main contribution is to expose the double discrimination endured by women in the region. Indeed, the results indicate that women are highly discriminated in the job market and undertake most of the domestic activities in the household, allocating in average 40 hours per week to paid market activities and another 40 hours to in-home unpaid activities. The indigenous populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 27 publications
1
24
0
3
Order By: Relevance
“…It is stronger when one takes into account that ethnic minorities face pre-market discrimination. They have, in general, limited access to education and health services, and are concentrated mainly in rural areas (Canelas and Salazar 2014;Atal et al 2009).…”
Section: Salaried Workersmentioning
confidence: 99%
“…It is stronger when one takes into account that ethnic minorities face pre-market discrimination. They have, in general, limited access to education and health services, and are concentrated mainly in rural areas (Canelas and Salazar 2014;Atal et al 2009).…”
Section: Salaried Workersmentioning
confidence: 99%
“…In other regions of the world, educational inequality between genders is lower due to both the vast educational expansion that took place in the past decades and active gender equity promotion. In Latin America, for instance, female educational attainment is on average higher than that of males; however, this gain has not yet been translated into lower inequalities in other socioeconomic spheres, such as the labour market, domestic production, and political representation (see Campana et al, 2018;Canelas & Salazar, 2014;Carrillo, Gandelman, & Robano, 2014).…”
Section: Educational Attainmentmentioning
confidence: 99%
“…Using more recent household surveys for Bolivia, Ecuador, and Guatemala, Canelas and Salazar (2014) show that in the three countries, indigenous workers are paid less than non-indigenous workers and that nearly half of the wage gap is explained by differences in human capital endowments. Similarly, Atal, Ñopo, and Winder (2009), using data for 18 Latin Americans countries, found that ethnic wage differences are greater than gender differences and that educational attainment differentials play an important role in explaining the gap.…”
Section: Related Literaturementioning
confidence: 99%